Biomechanical analysis of maximal instep kick by female soccer players - Shan, G.; Daniels, D.; Wang, C.; Wutzke, C.; Lemire, G. (Journal of Human Movement Studies, 2005)
This study used 3D miotion capture and full-body biomechanical modeling to examine soccer kicking done by females. The goal was to reveal the effects of long-term training by comparing novices with skilled athletes. The data collection technology consisted of a Vicon(tm) 3D motion capture System with 9 high-speed cameras (120 Hz) and wireless electromyography (EMG). Twenty female subjects (10 skilled, 10 novices), ranging in age from 19 to 24, were measured executing the maximal instep soccer kick. Results show effective upper-body movement to be a key factor in creating optimal initial conditions for more explosive muscle contraction during kicking. The EMG results also reveal that skilled players employ muscle control in a way that produces more rapid acquisition of maximal contractions and more accurate timing of the gross movement pattern. It can be concluded that long-term training leads to a control pattem which optimizes muscle lengths and contributes to explosive muscle activation for obtaining higher ball release velocity.